Background Vocabulary of the Russian Language - Khanova D. B. (European Science Publishing, 2023)
The linguo-cultural concept of background knowledge and their classification are considered, the classification of vocabulary with national-cultural semantics as a means of mastering background knowledge is analyzed. On the basis of this, the parameters of deobjectification of the national and cultural specificity of the lexical unit are determined, and new types of vocabulary with national and cultural semantics are distinguished.
Keywords: linguistic and cultural studies, background knowledge, vocabulary with national cultural semantics.